(untitled) (World Bulletin of Social Sciences, 2024)
This article converses about the views and aspects on the evolution and development of the Japanese language. There are probably more disputes about the origin of the Japanese language than about the age-old question of the primacy of the chicken or the egg. Unambiguous conclusion regarding his origins and genetic relatedness to others there are no languages to this day. This is one of the reasons why Japanese belong to the isolated group. This ambiguity has given rise to a large number of competing theories that consider ethnogenesis in different aspects language. The Japanese language, with its rich history and unique linguistic features, has undergone an exciting evolution and development over the centuries. From its origins in ancient Japan to its modern forms, the Japanese language reflects the dynamic cultural and social changes that have shaped the nation. In this article, we will delve into the journey of the Japanese language, exploring its origins, influences, and important milestones that contributed to its modern complexity